2020
DOI: 10.1016/j.ijhydene.2019.11.102
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculations of iron - vanadium carbide interfaces and the effect of hydrogen

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…The H atom solution energy of a C vacancy is the lowest among all the sites, suggesting that the C vacancy is the most stable hydrogen trapping site. 33,34 Nevertheless, the hydrogen trapping behavior has been considered only for the condition of the single site in the above studies, while that of the complex sites has rarely been considered. But it contributes to understanding the strong binding effect of the C vacancy on hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The H atom solution energy of a C vacancy is the lowest among all the sites, suggesting that the C vacancy is the most stable hydrogen trapping site. 33,34 Nevertheless, the hydrogen trapping behavior has been considered only for the condition of the single site in the above studies, while that of the complex sites has rarely been considered. But it contributes to understanding the strong binding effect of the C vacancy on hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The coherent interface between the carbide nano-precipitates and the bcc Fe matrix follows the Baker-Nutting (B-N) orientation relationship with (001) Fe ||(001) MC and [100] Fe ||[110] MC . 32,38,43 Based on the B-N orientation relationship, the coherent interfaces between carbides (VC, TiC, and NbC) and 2 Â 2 bcc Fe were constructed. The coherent interfacial structures between a-Fe and nano-precipitates were constructed and the strain was initially imposed on a-Fe.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The composition of the carbides plays an important role in H trapping energetics. A systematic comparison between chemically distinct MC carbides regarding the H trapping energetics at the coherent interfaces between precipitates and the BCC-Fe matrix can be obtained from the literature [49,50]. Ma et al [51] reported that the E b values of different precipitate interfaces are associated with the volume of H-located tetrahedron and the number of charges H gained from surrounding atoms.…”
Section: Carbide Precipitatesmentioning
confidence: 99%